Epithelioid inflammatory myofibroblastic sarcoma treated with ALK inhibitor: a case report and review of literature - Liu, Qiuyu (Int J Clin Exp Pathol, 2015)
Epithelioid inflammatory myofibroblastic sarcoma is extremely rare and belongs to a variant of inflammatory myofibrobalstic tumor with aggressive clinical course. We describe a case of a 22 years old man presented with an abdominal huge tumor. Microscopically, the neoplasm cells were rounded and epithelioid in shape. Abundant interstitial edema and less myxoid stroma were also present together with an inflammatory infiltrate. Fluorescence in situ hybridization revealed that ALK gene presented mutation. After surgery the patient received chemotherapy with an anaplastic lymphoma kinase (ALK) inhibitor, crizotinib. The patient continues to be alive with disease for 16 months and has no recurrence. Although EIMS has a poor prognosis, this is the few successful case with sustained response of targeted therapy.